2016
DOI: 10.1161/circulationaha.115.008728
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Control of Cardiovascular Disease in the Rapidly Changing Economy of China

Abstract: With one fifth of the world’s total population, China’s prevention and control of cardiovascular disease (CVD) may affect the success of worldwide efforts to achieve sustainable CVD reduction. To understand China’s current cardiovascular epidemic, requires awareness of the economic development in the past decades. The rapid economic transformations (industrialization, marketization, urbanization, globalization, and informationalization) contributed to the aging demography, unhealthy lifestyles, and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 99 publications
2
99
0
Order By: Relevance
“…The study (31) also demonstrated that current dietary recommendations were only based on the assumption of a linear association between saturated fatty acid intake and LDL cholesterol, and the subsequent positive relationship between LDL cholesterol and cardiovascular disease, without considering that higher intake of saturated fatty acids were also related to higher HDL cholesterol, lower triglycerides, lower total cholesterolto HDL ratio. Besides, participants with disease might shift their unhealthy lifestyles in a beneficial direction after knowing their own physical condition, which might have influenced our results (32).…”
Section: Discussionmentioning
confidence: 99%
“…The study (31) also demonstrated that current dietary recommendations were only based on the assumption of a linear association between saturated fatty acid intake and LDL cholesterol, and the subsequent positive relationship between LDL cholesterol and cardiovascular disease, without considering that higher intake of saturated fatty acids were also related to higher HDL cholesterol, lower triglycerides, lower total cholesterolto HDL ratio. Besides, participants with disease might shift their unhealthy lifestyles in a beneficial direction after knowing their own physical condition, which might have influenced our results (32).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the unhealthy eating patterns and physical inactivity, an alarming increase in overweight and obesity has been seen over the past decades in China 27. In addition, the ageing of the population and the changes in lifestyle have also led to a dramatic rise in prevalence of hypertension, diabetes and dyslipidaemia 25. For reasons given above, the ideal CVH metrics in Chinese population must have changed a great deal.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid economic expansion and increasing average life expectancy, CVD has become the leading cause of death in China, and its morbidity and mortality has been increasing since the late 1980s. Currently, CVD accounts for up to 40% of all deaths in both urban and rural populations in China [5]. …”
Section: Introductionmentioning
confidence: 99%